Intimate partner violence against women in Nigeria: a multilevel study investigating the effect of women's status and community norms - Faith Owunari Benebo; Barbara Schumann; Masoud Vaezghasemi (BMC, 2018)
Abstract Background Intimate partner violence (IPV) against women has been recognised as a public health problem with far-reaching consequences for the physical, reproductive, and mental health of women. The ecological framework portrays intimate partner violence as a multifaceted phenomenon, demonstrating the interplay of factors at different levels: individual, community, and the larger society. The present study examined the effect of individual- and community-level factors on IPV in Nigeria, with a focus on women's status and community-level norms among men. Methods A cross-sectional study based on the latest Nigerian Demographic Health Survey (2013) was conducted involving 20,802 ever-partnered women aged 15-49 years. Several multilevel logistic regression models were calibrated to assess the association of individual- and community-level factors with IPV. Both measures of association (fixed effect) and measures of variations (random effect) were reported. Results Almost one in four women in Nigeria reported having ever experienced intimate partner violence. Having adjusted for other relevant covariates, higher women's status reduced the odds of IPV (OR = 0.47; 95% CI = 0.32-0.71). However, community norms among men that justified IPV against women modified the observed protective effect of higher women's status against IPV and reversed the odds (OR = 1.89; 95% CI = 1.26-2.83). Conclusions Besides women's status, community norms towards IPV are an important factor for the occurrence of IPV. Thus, addressing intimate partner violence against women calls for community-wide approaches aimed at changing norms among men alongside improving women's status.